2002
DOI: 10.1088/0022-3727/35/18/313
|View full text |Cite
|
Sign up to set email alerts
|

Physics of lubricated impact of a sphere on a plate in a narrow continuum to gaps of molecular dimensions

Abstract: This paper investigates the phenomenon of lubricated impact dynamics of ellipsoidal bodies upon semi-infinite elastic solids, giving rise to Hertzian contact conditions. The analysis conforms to the numerical predictions and experimental findings of others, when the physics of motion of the lubricant can be described through Newtonian continuum mechanics, with the dominant viscous action embodied in the transient solution of Reynolds' equation. The equivalence of squeeze film action under impacting conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 35 publications
(72 reference statements)
4
41
0
Order By: Relevance
“…The numerical studies by Al-Samieh & Rahnejat (2002) calculated the pressure increase and surface deformation for a particle impacting a surface coated with a thin liquid layer. By coupling the equation for the motion of the liquid layer with the motion of the particle and the elasticity of the solid surfaces, the authors were able to calculate the pressure rise and compared it with the experiments by Safa & Gohar (1986).…”
Section: Introductionmentioning
confidence: 99%
“…The numerical studies by Al-Samieh & Rahnejat (2002) calculated the pressure increase and surface deformation for a particle impacting a surface coated with a thin liquid layer. By coupling the equation for the motion of the liquid layer with the motion of the particle and the elasticity of the solid surfaces, the authors were able to calculate the pressure rise and compared it with the experiments by Safa & Gohar (1986).…”
Section: Introductionmentioning
confidence: 99%
“…With this assumption taken into account, it is clear that the cavitated region is governed by a balance between the squeeze film effect (the ultimate term in the last equation) and the drainage of the fluid from the contact on the account of hydrodynamics alone. Separation of the surfaces on account of squeeze; ∂θh/∂t > 0 increases the chance of cavitation, which is the same as an increase in the speed of entraining motion (Al-Samieh and Rahnejat [11]). One should then expect reduced cavitation at lower sliding speeds as an outcome of the analysis, which would encourage better lubricant distribution on the free surface post film reformation.…”
Section: Hydrodynamic Pressurementioning
confidence: 99%
“…Matsuoka and Kato [5], Abd Al-Samieh and Rahnejat [4] and Al-Samieh and Rahnejat [1,11] also assumed the same for the bulk hydrodynamic behaviour of the lubricants such as those described above and used in the current analysis. Clearly, for the cavitated region: ρ = ρ c when p = p c .…”
Section: Hydrodynamic Pressurementioning
confidence: 99%
“…Al-Samieh and Rahnejat [27] showed that the monitored pressure spike could be predicted accurately once these issues were adequately addressed. Their predictions agreed well with the measured pressure distributions for a ball bearing falling freely upon an oily glass plate upon which Safa and Gohar [28] had fabricated a manganin micro-transducer.…”
Section: Introductionmentioning
confidence: 99%